Date palm‐derived graphene materials: a review on recent advances in synthesis, characterization and environmental applications - Malaz Suliman; Muhammad Tahir (Frontiers in Nanotechnology)
Recent research has increasingly focused on finding low-cost, eco-friendly sources to produce high-quality materials. Since its discovery, graphene has garnered significant attention due to its exceptional properties. However, large-scale production of graphene remains challenging due to the expensive and harmful reagents typically used in its synthesis. Agricultural waste, a rich carbon source, offers a potential solution, with date palm trees generating substantial amounts of waste annually. This review is the first comparative study that systematically explores graphene materials derived from date palm trees, date seeds, and date syrup, emphasising their environmental applications. The paper begins by explaining the basics of graphene and various synthesis approaches from solid waste and different derivatives. It covers the properties of graphene and how various parameters can alter these characteristics. The primary focus is on the synthesis, characterization, and properties of graphene derived from date palm waste. A comparative analysis of graphene derived from date palm versus oil palm is also provided. The environmental applications of graphene produced from date palm waste are discussed in detail. Additionally, the paper outlines the prospects and future opportunities for producing graphene from date palm waste. In summary, graphene materials derived from date palm waste showed superior properties and exceptional adsorption capacities in pollutant removal. Although research in this area is still in its early stages, the pressing need for sustainable graphene production methods is expected to drive significant advancements in this field and this pioneering review can provide a roadmap for researchers.